35 The outcome for children following their first presentation with heart failure to a transplantation unit between 2010 – 2015. (2nd February 2018) - Rico-Armada, A; Crossland, D; Hermuzi, A; Sajnach-Menke, M; Reinhardt, Z; O'Sullivan, J
Abstract : Purpose: Most reports on the outcome of children who present with heart failure are from an era when ventricular assist devices (VAD) were not available. This study provides outcome data for the modern era where prolonged circulatory support can be considered for children of all ages. Methods: Data on children who presented from 2010–2015, with a first diagnosis of heart failure, excluding those with structural heart disease, was retrieved. Results: The median age at presentation, in the 100 children, was 18 months. Overall, hospital mortality was 15%, 50% received a heart transplant, 25% recovered systolic function and 15% stabilised on oral therapy. Mean time from admission to death was 89 days. Most children (63%) were <5 years old and most of the deaths (11/15) occurred in that group. Comparing age groups: mortality was higher (19% versus 8%); transplantation rate was lower (41% versus 65%); VAD use higher (62% versus 48%) and more recovered systolic function (29% versus 19%) in the <5 years versus those ≥5 years. The mean duration of VAD, in those who died in the <5 year group, was 106 days (compared to 61 days in those who survived). Conclusion: Heart failure in children which requires referral to a transplant unit remains a very serious illness with a high chance of either transplantation or death. Modifications to the current VAD support will be required to enable this group to survive to either recovery or access to the inadequate heart donor pool.